Social Cyberspace (Journal of University of Babylon for Engineering Sciences, 2024)
Architecture has evolved from being physical spaces to cyber spaces, and physical architecture has been oscillating between cyber spaces. However, with the development of cyberspaces, it has become sometimes ahead of and sometimes lagging behind physical spaces, so the representation of physical spaces as cyberspaces has become used for several purposes, and its applications have been used in several fields, such as the military, medical sector, distance tourism, and others. It did not address the social aspects of these spaces, so this study came to study the social aspects. Therefore: the research problem is (exploring the social aspect of cyberspaces) and the research objectives emerged (developing cyberspace mechanisms to create social space).The research approach was represented by several procedures to achieve the goal and solve the research problem by building a theoretical framework and applying it on a virtual space to reach the results.The research found several mechanisms to achieve the social aspects of cyberspace: participation, representation, flexibility, immersion, realism, transfer, adaptation, and personal differences between individuals. It also affects the feeling of abandonment of real environments more. Ages between 19-40 feel that they are separated from the real environment, while ages 40 And above, they cannot abandon the real environment despite their sense of presence in the virtual environment, and the number of senses contributes to the user’s more immersion in the experience, and the sense of sight achieves a higher presence than the rest of the senses, and the senses result in the production of a sense of presence, such as those of sight, hearing, touch and smell.